HibahQu Education Monitoring Platform Based on Human-Centric Orange Technology Laravel 12 Vue.js - Untung Rahardja; Lod Sulistyo; Dwi Safarina; Muhamad Rapidan Kusuma; Nur Silawati; Zeze Nanle (ADI Publisher, 2025)
The digital transformation of grant management in higher education is essential to enhance transparency, efficiency, and accountability in research and community service programs. However, many institutions still depend on frag mented monitoring mechanisms, limited real-time information access, and systems that are not fully user oriented, leading to in effective supervision and delayed decision making. This study aims to design and develop a higher education grant monitoring platform based on Human-Centric Orange Technology to support real-time tracking, structured reporting, and process transparency across the grant lifecycle. The research adopts a system development approach combined with qualitative analysis, including requirement analysis, system design, implementation, and user evaluation through interviews and direct observations involving academic and administrative stakeholders. This approach enables a comprehensive understanding of user needs, usability considerations, and system relevance within the institutional grant management context. The findings indicate that the proposed platform improves monitoring effectiveness through real-time grant status visualization, transparent information access, and integrated reporting features, while enhancing user experience through an intuitive, role based, and human centric interface. The study concludes that implementing a Human-Centric Orange Technology based monitoring platform can strengthen grant governance, improve transparency, and optimize administrative efficiency in higher education institutions in a user oriented manner.